STRATEGI UMKM PT IJO KREASI INDONESIA PASCA PANDEMI COVID-19 - Dhiyaa, Aqila Ratna; Sulistyowati, Lies (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
PT Ijo Kreasi Indonesia is an Agribusiness MSME that has experienced a decrease in income due to the Covid-19 pandemic. In the post-pandemic period, Indonesia's macroeconomic situation has started to improve as seen from the increase in national GDP in 2022. However, if we look at it from a micro perspective, PT ljo Kreasi Indonesia has not experienced an increase in income in the post-pandemic period. Therefore, PT ljo Kreasi Indonesia needs a strategy so that it can increase its income again. The purpose of this research is to formulate the right strategy for PT Ijo Kreasi Indonesia so that it can develop in the post-pandemic period. This study uses a qualitative method with a case study technique. The analysis techniques in this study are descriptive analysis and IFE, EFE, IE, SWOT and QSPM analysis to formulate strategies. The results of the research based on the IE matrix show that PT Ijo Kreasi Indonesia is in cell 1 which indicates the company is in the growth and development phases. The alternative priority strategy that can be implemented by PT Ijo Kreasi Indonesia based on the results of the QSPM matrix is to maintain and maintain product quality with a TAS value of 5.926.